Gertrude Stein and Richard Wright : The Poetics and Politics of Modernism - Weiss, M. Lynn (Book collections on Project MUSE., 1998)
Gertrude Stein and Richard Wright began their careers as marginals within marginalized groups, and their desire to live peacefully in unorthodox marriages led them away from America and into permanent exile in France. Still, the obvious differences between them - in class, ethnic and racial origins, and in artistic expression - beg the question: What was there to talk about? This question opens a window onto each writer's meditations on the influence of racial, ethnic, and national origins on the formation of identity in a modern and post-modern world.